Representation of minority linguistic groups by broadcast media in Zimbabwe: a case of Star FM programme-mother tongue march - Mapuranga, Tinashe (Midlands State University, 2019)
The study focuses on the representation of minority linguistic groups by broadcast media in Zimbabwe paying particular attention to Star FM programme ‘Mother Tongue March (MTM). The research explores the role of Star FM in promoting local languages. The Public Sphere and the Democratic Participant theory were employed to provide a theoretical base for this research. The study made use of qualitative research method, which was complemented by the use of open-ended questionnaires and interviews to have more detailed information when collecting and analyzing data. The research found that Star FM is making efforts to accommodate everyone on the public sphere through the programme ‘ Mother Tongue March’. However besides MTM, there are no other specific programs dedicated for indigenous languages. The study recommends Star FM to recruit presenters that speak different local languages. The government can also be recommended to come up with policies that can help improve the participation of minority linguistic groups on the media e.g students must be taught using local languages in the education sector.